2016
DOI: 10.1093/jac/dkw236
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of MDR MRSA between primates, their environment and personnel at a United States primate centre

Abstract: Objectives: MDR MRSA isolates cultured from primates, their facility and primate personnel from the Washington National Primate Research Center were characterized to determine whether they were epidemiologically related to each other and if they represented common local human-associated MRSA strains.Methods: Human and primate nasal and composite environmental samples were collected, enriched and selected on medium supplemented with oxacillin and polymyxin B. Isolates were biochemically verified as Staphylococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(85 citation statements)
references
References 27 publications
9
76
0
Order By: Relevance
“…We found high proportions of ST5 and ST59 in this study and these STs were also globally reported in communities [27]. We also found hospital-(ST188) [28,29] and livestock-(ST398) [30,31] associated STs in this study. The results of CCs and STs for S. aureus isolates could demonstrate the multiple transmissions among human beings, livestock and environment, which are similar to previous studies [6,24].…”
Section: Discussionsupporting
confidence: 80%
“…We found high proportions of ST5 and ST59 in this study and these STs were also globally reported in communities [27]. We also found hospital-(ST188) [28,29] and livestock-(ST398) [30,31] associated STs in this study. The results of CCs and STs for S. aureus isolates could demonstrate the multiple transmissions among human beings, livestock and environment, which are similar to previous studies [6,24].…”
Section: Discussionsupporting
confidence: 80%
“…We found high proportions of ST5 and ST59 in this study and these STs were also globally reported in communities [26]. We also found hospital-(ST188) [27,28] and livestock-(ST398) [29,30] associated STs in this study. Additionally, according to the results of SCCmec types we could also know the source of MRSA isolates were from both communities and healthcare settings, which is similar to the observed studies [4,9].…”
Section: Discussionsupporting
confidence: 80%
“…1 The first, ST188-MRSA-IV, had 23 previously been reported in humans and primates, whereas the second, ST3268-24 MRSA-V, had initially been discovered in quarantined primates originating outside 25…”
Section: Text 19mentioning
confidence: 99%
“…1 We had also identified ST3268-MRSA-V and its single-locus variant 27 (SLV) ST2817-MRSA-V among long-tailed macaques (Macaca fascicularis) used in 28 experimental surgery in 2014, and describe our experience here, comparing our 29 isolates to the two U.S. ST3268 isolates via genomic analysis. 1 …”
Section: Text 19mentioning
confidence: 99%